Provenance and archaeometric analysis of late Roman glass from the Palatine Hill - Storozhylova, Yuliia (2021)
ABSTRACT: The aim of this thesis was to perform an archaeometric study of the collection of glass fragments, found during excavation of layers dated 6th-7th century AD of a room XII, 1 of the Horrea Vespasians, a complex of warehouses during the Imperial period on the Palatine Hill. These glass fragments were excavated only in 2017 and this is the first study that involves them. A non-destructive approach to study elemental composition of the fragments was chosen. A characterization of the glass fragments was performed by XRF and LA-ICP-MS. In this study, an attempt to reconstruct the production process with possible raw materials and colorants used was made. The results obtained in this study will contribute to the literature on Roman glass production,